Regulation of Adaptive Immunity; The Role of Interleukin-10 - Ng, T.H. Sky; Britton, Graham J.; Hill, Elaine V.; Verhagen, Johan; Burton, Bronwen R.; Wraith, David C. (Frontiers in Immunology, 2013)
Since the discovery of interleukin-10 (IL-10) in the 1980s, a large body of work has led to its recognition as a pleiotropic immunomodulatory cytokine that affects both the innate and adaptive immune systems. IL-10 is produced by a wide range of cell types, but for the purposes of this review we shall focus on IL-10 secreted by CD4+ T cells. Here we describe the importance of IL-10 as a mediator of suppression used by both FoxP3+ and FoxP3- T regulatory cells. Moreover, we discuss the molecular events leading to the induction of IL-10 secretion in T helper cell subsets, where it acts as a pivotal negative feedback mechanism. Finally we discuss how a greater understanding of this principle has allowed for the design of more efficient, antigen specific immunotherapy strategies to exploit this natural phenomenon clinically.